Vitrectomy With Silicone Oil Tamponade and Without Internal Limiting Membrane Peeling for the Treatment of Myopic Foveoschisis With High Risk of Macular Hole Development - Yao, Yuou; Qu, Jinfeng; Shi, Xuan; Hu, Jie; Hou, Jing; Miao, Heng; Cheng, Yong; Zhao, Mingwei (Frontiers in Medicine, 2021)
Purpose: To explore the efficiency and safety of the surgical procedure of pars plana vitrectomy (PPV) with silicone oil (SO) tamponade and without internal limiting membrane (ILM) peeling for myopic foveoschisis (MF) eyes with high risk of macular hole formation. Methods: Three eyes (three patients) with MF and foveal detachment were enrolled into the study. Comprehensive preoperative ophthalmological assessments, including best corrected visual acuity (BCVA) and spectral-domain optical coherence tomography (SD-OCT) were performed on the eyes. Central foveal thickness (CFT) and thickness of continuous neurosensory retina at foveola were measured. All patients underwent PPV followed by SO tamponade and without ILM peeling. SO was removed when MF and retinal detachment were resolved. Patients were followed up postoperative at month 1, 3, 6, and 12. Results: All the three eyes achieved complete resolution of MF and foveal reattachment with an average SO tamponade period of 11.67 ± 0.58 months. The average CFT at 6 months was 91 ± 27.5 μm, hence reduced significantly from baseline at 365.3 ± 137.85 μm (P = 0.037). There was no postoperative macular hole formation despite the average preoperative sensory retina thickness of 58 ± 20.07 μm. Mean BCVA was improved from logMAR 1.43 ± 0.75 to logMAR 0.8 ± 0.75 on the last follow-up. Manageable SO-related complications were reported, including SO emulsification, ocular hypertension, and cataract. Conclusion: Vitrectomy with SO tamponade and without ILM peeling as an optional surgical protocol to treat MF is effective and safe, especially for MF eyes vulnerable to macular hole formation.